Balancing mass transport resistance and membrane resistance when tailoring microporous layer thickness for polymer electrolyte membrane fuel cells operating at high current densities. (10th January 2016) - Antonacci, P.; Chevalier, S.; Lee, J.; Ge, N.; Hinebaugh, J.; Yip, R.; Tabuchi, Y.; Kotaka, T.; Bazylak, A.
Abstract: Synchrotron X-ray radiography and electrochemical impedance spectroscopy (EIS) were concurrently used to quantify the effects of varying MPL thickness on PEMFC performance. Increasing the MPL thickness from 30 μm to 50 μm was found to lower the liquid water volume by 8% in the cathode substrate, which resulted in a 50% decrease in the oxygen mass transport resistance at a current density of 2.0 A/cm 2 . Increasing the MPL thickness beyond 50 μm at the same current density did not lead to any further substantial reductions of the liquid water volume in the cathode substrate (2%); however, the ohmic resistance increases significantly (16%). Among the four MPL thicknesses studied, the 50 μm-thick MPL provides an optimized trade-off between the hydration of the membrane and the liquid water content in the fibrous substrate. A key observation of this work is the significant influence that high current density operation has on the heat and water management of polymer electrolyte membrane fuel cells.